An Analysis of Students’ Grammatical Errors on Speaking at SEA Debate at English Department of Faculty of Languages and Arts of Universitas Negeri Padang - Stephanie Chania; Zul Amri (Journal of English Language Teaching, 2019)
The purpose of this study was to analyze students’ grammatical errors on speaking at SEA Debate at English Department of Faculty of Languages and Arts of Universitas Negeri Padang. It employed qualitative research method with the Debate class of 2017 students as the research population. There were six students taken as the research sample selected through purposive sampling technique. The data were collected through smart-phone video recorder and interview guideline. The video recording was transcribed and analyzed from the first speaker until the last speaker. After analyzing the data, the students were interviewed to support the data in order to answer the research question of the study. The collected data were mainly in the form of transcription texts mined from the recordings of the debate as well as the interview of each student. The results of the study showed the most type of errors made by the SEA Debate students was omission error which consisted of 77 errors or 50.66% of errors. The causes of errors were affected by the students were inadequate learning, overgeneralization, and simplification. Key words: Speaking, Grammatical Error, Debate